The active tectonics of the Vuoksi Fault Zone in the Karelian Isthmus: parameters of paleoearthquakes estimated from bedrock and softsediment deformation features - S.V. Shvarev; A.A. Nikonov; M.V. Rodkin; A.V. Poleshchuk (Bulletin of the Geological Society of Finland, 2018)
The area under study is located in the south-eastern periphery of the Fennoscandian crystalline shield. At present this is a tectonically quiet region without large seismic events. But it is well known that in post-glacial time the Fennoscandian shield was an arena of active postglacial tectonics and large earthquakes. The evidence for such events was found in various parts of Fennoscandia. The traces left by some paleoearthquakes show an undisputed character of large post-glacial faults some tens of kilometres long and of a few meters in displacement. However, some other features left by earthquakes are under discussion. Numerous deformations in bedrock and in soft sediments which can be considered as being due to earthquakes were found in the Russian Karelia. Interpretation of some of these deformation structures can lead to different conclusions about their origin, for example, weathering, cryogenic, glacial, and gravitational factors. One possible way to overcome these difficulties is an integrated study of different types of deformations at key sites, comparison of these with each other and with the tectonic features of the region, and the search for common structural and kinematic features. Another problem is the estimation of parameters of paleoearthquakes. This problem includes the determinations of their location, intensities, magnitudes, and age. The key site under study is located in the northern part of the Karelian Isthmus in the re-activated (during post-glacial time) tectonic zone (the Vuoksi Fault Zone), whose signature in the relief is seen in the form of the straight-line valley of the Vuoksi River. We studied different types of post-glacial seismogenic deformations at this locality. There are seismically induced gravitational and vibrational deformations in solid rock, as well as folds and ruptures in loose sediments. The key site of large deformation examined here includes three zones: 1) the main zone of deformations or the Central Fractured Massif (CFM); 2) the seismically induced colluvial ...